Associations of neutrophil-percentage-to-albumin ratio level with all-cause mortality and cardiovascular disease-cause mortality among patients with hypertension: evidence from NHANES 1999–2010 - Liu, Zhihao; Dong, Lei; Shen, Geng; Sun, Yangyang; Liu, Yuting; Mei, Jiarong; Jia, Jia; Fan, Fangfang; Wang, Wenye; Huang, Wei; Li, Jianping (Frontiers in Cardiovascular Medicine, 2024)
Background The associations of neutrophil-percentage-to-albumin ratio (NPAR) level with all-cause and cardiovascular disease (CVD)-cause mortality among patients with hypertension remain unclear. This study aims to investigate the associations of NPAR level with all-cause and CVD-cause mortality among patients with hypertension. Methods This prospective cohort study included 8,990 patients with hypertension who participated in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2010. Multivariable Cox proportional hazards regression models were used to compute hazard ratios and 95% CIs for the associations of NPAR level with all-cause mortality and CVD-cause mortality. Restricted cubic spline analyses were used to examine the nonlinear association of NPAR level with all-cause mortality and CVD-cause mortality. Results This cohort study included data from 8,990 participants in analysis. During 104,474 person-years of follow-up, 3,069 all-cause deaths and 1,449 CVD-cause deaths were documented. Nonlinear associations were observed for NPAR levels with risk of all-cause mortality and CVD-cause mortality among patients with hypertension. Compared with participants in T1 of NPAR, there was a significantly increased risk of all-cause mortality and CVD-cause mortality for participants in both T2 and T3 in the fully adjusted model (model 3). The corresponding HRs for all-cause mortality were 1.10 (95% CI, 0.98–1.22) and 1.63 (95% CI, 1.45–1.82). The corresponding HRs for CVD-cause mortality were 1.10 (95% CI, 0.99–1.23) and 1.63 (95% CI, 1.46–1.81). Conclusions Elevated NPAR level was significantly associated with an increased risk of all-cause and CVD-cause mortality in adults with hypertension. NPAR may be clinically useful for predicting long-term health outcomes and mortality in hypertensive population.